Blurring the Boundaries: Fourteen Great Detective Stories and Joyce's A Portrait of the Artist as a Young Man in the Modern Library Series. - Jaillant, Lise (James Joyce Quarterly)
This article examines the simultaneous publication of James Joyce's A Portrait of the Artist as a Young Man and a collection of detective stories in the Modern Library series in March 1928. The Modern Library, a uniform series of reprints sold for only 95 cents, did not make any difference between the two books. Not only did they share a similar physical format, but they were also advertised in the same periodicals, and reviewers showed no surprise at the juxtaposition of "high" and "low" culture. Drawing on extensive research in Random House archives at the Columbia Rare Book and Manuscript Library, this essay uses a book-history approach to show that the Modern Library contributed to the blurring of boundaries between modernist and popular fiction.